UMPSA welcomes UI and UNAIR Indonesia delegates - Nur Syafiqah, Fauzan (UMPSA, 2024)
GAMBANG, 19 August 2024 – A total of 20 students, along with three accompanying staff from the Universitas Indonesia (UI) and Universitas Airlangga (UNAIR), participated in the seven-day International Inbound Mobility Programme starting on 18 August 2024 at the Faculty of Industrial Sciences and Technology (FSTI), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).